STUDI UBAHAN BATUAN TIPE SKARN DI DESA PAGERJURANG, KECAMATAN BAYAT, KABUPATEN KLATEN, PROPINSI JAWA TENGAH - , ATMA GALIH DHARMAWAN, Dr. Lucas Donny Setijadji S.T, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Jiwo Hills area in the Bayat District, Klaten Regency, Central Java Province is a relatively small area but with a complex geological condition. Some of the oldest rocks in Java, that consist of metamorphic rocks and Paleogene sedimentary rocks, are exposed in this area. Metamorphism is generally of a regional metamorphism style characterized by the presence of mica schist. However, at Pagerjurang village we found a contact metamorphism as indicated by the occurence of skarn rocks. Skarn is likely to be formed by contact metamorphism and metasomatism by hydrothermal solutions derived from magma (intrusion) that affected limestone and siltstone. Characteristics of mineralogy and mineral paragenesis of the skarn are studied by petrography, mineragraphy, and XRD analysis on rock samples representing different zone of prograde and retrograde skarn. Skarn alteration and mineralization focus at the bedding contact of limestone and siltstone, that has been altered to marble and hornfels. Mineralization is controlled by the NE-SW and NWSE trending geological structures, there are Melikan Dextral Strike Slip Fault and Pagerjurang Sinistral Strike Slip Fault. The skarn can be divided into three zones, namely 1) proximal prograde exoskarn zone characterized by the presence of garnet (grossular) more abundant than clinopyroxene (wollastonite-augitediopside- hedenbergite)